2011
DOI: 10.1002/eji.201141666
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β signaling via Smad4 drives IL‐10 production in effector Th1 cells and reduces T‐cell trafficking in EAE

Abstract: SUMMARY Effector Th1 cells perpetuate inflammatory damage in a number of autoimmune diseases, including MS and its animal model EAE. Recently, a self-regulatory mechanism was described where effector Th1 cells produce the immunomodulatory cytokine IL-10 to dampen the inflammatory response in both normal and autoimmune inflammation. While the presence of TGF-β has been suggested to enhance and stabilize an IFN-γ+IL-10+ phenotype, the molecular mechanism is poorly understood. Additionally, in the context of adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…However, TGF-β clearly plays a critical role in the development of CD4 + regulatory cells, which would be consistent with the observation that administration of TGF-β results in amelioration of disease. It has also been shown that TGF-β has a regulatory effect on encephalitogenic Th1 cells (Huss et al, 2011; 2010), further supporting the dominant immunosuppressive role of TGF-β in autoimmune demyelinating disease.…”
Section: Discussionmentioning
confidence: 85%
“…However, TGF-β clearly plays a critical role in the development of CD4 + regulatory cells, which would be consistent with the observation that administration of TGF-β results in amelioration of disease. It has also been shown that TGF-β has a regulatory effect on encephalitogenic Th1 cells (Huss et al, 2011; 2010), further supporting the dominant immunosuppressive role of TGF-β in autoimmune demyelinating disease.…”
Section: Discussionmentioning
confidence: 85%
“…High levels of MMP-9 have previously been reported to predict [28], and in agreement with our results reflect [29], MRI activity in MS. A similar trend, although not significant after Bonferroni correction, was recorded for TGFβ1. It is believed that the main role of TGFβ1 is to maintain immune tolerance and that it protects against inflammatory demyelination [30,31]. However, recent studies suggest that TGFβ1 could induce the generation of autoreactive Th17 cells [32], a subset believed to promote disease activity in MS.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were stimulated with LPS (100 ng/ml) in the presence or absence of DMF (70 M) for 24 h. Supernatants were then removed, and DCs were washed twice in warm PBS. MOG Cytokine ELISA-Supernatants were collected for each culture condition and analyzed for IL-12p70, IL-6, IFN-␥, and IL-17 as described previously (15). ELISA was performed using purified anti-mouse capture antibodies and biotinylated rat anti-mouse detection antibodies (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Flow Cytometry and Intracellular Cytokine Staining-Flow cytometric analysis was performed to evaluate CD44 expression on T cells as described previously (15). In the co-culture, GolgiPlug (1 mg/ml; BD Biosciences) was used to block cytokine secretion for the last 4 h prior to staining.…”
Section: Methodsmentioning
confidence: 99%